PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN SUASANA TERHADAP KEPUASAN PELANGGAN DI J. SPARROW RESTORAN - Putri Juliana Lumban Tungkup; Bonifasius MH Nainggolan (Adisam Publisher, 2024)
This research aims to analyze the influence of product quality, service quality, and atmosphere on customer satisfaction at J.Sparrow, a well-known restaurant. Data was collected through a survey involving 132 respondents who were J.Sparrow customers. The data analysis method uses SPSS version 26 with multiple linear regression techniques to test the research hypothesis. The research results show that product quality, service quality, and atmosphere simultaneously and partially have a significant effect on customer satisfaction. Product quality has the most dominant influence compared to other variables. These findings indicate that improvements in product quality, friendly and efficient service, and a comfortable and attractive atmosphere can increase customer satisfaction levels. The implication of this research is that it is important for J.Sparrow management to continue to improve these three aspects in order to maintain and increase customer loyalty. This research also makes an academic contribution by enriching the literature on factors that influence customer satisfaction in the restaurant industry.